Comparison between Saliva and Nasopharyngeal Swabs for the Rapid Detection of Respiratory Viruses Using the Roche Cobas® Liat® Polymerase Chain Reaction System in Rural Guatemala - Paiz-Reyes, Claudia; Arias, Kareen; del Cid-Villatoro, Julio; Vásquez, Daniel; Gomez, Melissa; Rojop, Neudy; Mejia, Wanda; Lamb, Molly M.; Chu, May; Calvimontes Barrientos, Diva M.; Asturias, Edwin J.; Olson, Daniel (The American journal of tropical medicine and hygiene, 2025)
We evaluated the performance of saliva compared with nasopharyngeal (NP) swabs for the detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), influenza A/B, and respiratory syncytial virus (RSV) using the Roche cobas ® Liat ® point-of-care platform (Roche, Basel, Switzerland). Within an existing adult cohort in Guatemala, consenting participants with influenza-like illness (ILI) provided paired saliva and NP swabs, which were tested for SARS-CoV-2, influenza A/B, and RSV on the Liat platform. Among 138 ILI episodes from 123 enrolled subjects, 35/124 (28.2%), 5/135 (3.7%), 6/135 (4.4%), and 7/135 (5.2%) samples were reverse transcription polymerase chain reaction-positive for SARS-CoV-2, influenza A, influenza B, and RSV, respectively. For SARS-CoV-2, saliva/NP agreement was 90.3% (Cohen’s kappa = 0.731); 12 (9.7%) of the samples were discordant (three saliva-positive only, nine NP-positive only); and the median cycle threshold (Ct) for saliva was higher than that for NP (26.53 versus 23.54; P = 0.005). In our setting, saliva had a lower viral load correlate (Ct) but maintained a good correlation with NP swabs for the detection of SARS-CoV-2 on the Liat platform.